The Logic of Renewal : Evaluation at the World Bank (1992-2002) - Picciotto, Robert (World Bank, Washington, DC, 2014)
Modern psychology confirms that in order to adapt to the demands of a changing, sometimes hostile environment, and organisms must be able to profit from past experience. Therefore the textbook definition of learning is in three parts: (i) to find out how the operating environment works; (ii) to recognize signals about its evolution; and (iii) to adjust behavior in order to survive and adapt. It follows that periodic renewal that address all three aspects of learning are needed both for the World Bank and for its evaluation function. Thus, the history of the operations evaluation department (OED) renewal is the history of its capacity to learn, that is, (i) to adapt to the external and internal operating environment; (ii) to identify new evaluation priorities; and (iii) to put in place the programs, skills, and processes needed to implement them. OED renewal articulated five strategic objectives: (i) move evaluation to a higher plane; (ii) shorten the feedback loop and fill evaluation gaps; (iii) build evaluation capacity; (iv) invest in knowledge and partnerships; and (v) manage for results.